(untitled) (Педагогіка вищої та середньої школи, 2009)
In article the contents of concepts Із systematized: "educational technologies", "pedagogical technology», "suggestive-pedagogical technology", their contents and structure is opened, application of receptions and methods which will promote efficiency to educational process, is offered to development of imagination, self-control and self-expression.